Trans care - Malatino, Hil (Minneapolis : University of Minnesota Press, 2020)
"What does it mean for trans people to show up for one another, to care deeply for one another? How have failures of care shaped trans lives? What care practices have trans subjects and communities cultivated in the wake of widespread transphobia and systemic forms of trans exclusion? Trans Care is a critical intervention in the ways that care labor and care ethics have heretofore been thought, arguing that dominant modes of conceiving and critiquing the politics and distribution of care entrench normative and cis-centric familial structures and gendered arrangements. A serious consideration of trans survival and flourishing requires a radical rethinking of how care operates"--Back cover
Surviving trans antagonism -- Beyond burnout -- Theorizing trans care -- Something other than ancestors: history lessons -- Trans care within and against the medical-industrial complex.
Print version record.
Includes bibliographical references (pages 75-79).
JSTOR
Keywords: Transgender people -- Social conditions; Transgender people -- Health and hygiene; Transgender people -- Medical care; Queer theory; Transgenres -- Conditions sociales; Transgenres -- Santé et hygiène.; Transgenres -- Soins médicaux.; Théorie queer; Queer theory; Transphobia; Anti-transgender discrimination; Transgender activism; Transgender history; Transgender studies